Meniti Jalan Nasionalisasi Aset Perusahaan Belanda Di Indonesia: Menguntungkan Atau Merugikan - Danan Tricahyono (Criksetra: Jurnal Pendidikan Sejarah, 2021)
Indonesia as an independent country has aspirations of being independent, especially in the economic field. The steps taken include nationalizing various vital public buildings owned by foreigners with compensation payments. This study aims to analyze the path taken by the government to nationalize Dutch-owned companies. This study uses the historical method which consists of five steps: heuristics, source criticism, interpretation and historiography. The results of the study show that the nationalization of companies started from the period of the national movement leading to the concept of Indonesianization referring to Law Number 86 of 1958 concerning the Nationalization of Dutch- Owned Companies. The nationalized companies are engaged in agriculture and plantations, trade, industry and mining, banking, electricity and gas, transportation, and construction. The effects of nationalization were in the form of capital outflows, shaky balance sheets, and company administration. Companies that were nationalized in their journey turned into BUMN.